Does the Primary Resource of Sex Education Matter? A Swiss National Study. Issue 2 (12th February 2020) - Barrense-Dias, Yara; Akre, Christina; Surís, Joan-Carles; Berchtold, André; Morselli, Davide; Jacot-Descombes, Caroline; Leeners, Brigitte
Abstract : Sex education (SE) remains a subject of debate, including controversies on resources. The purpose of this paper was to determine the main SE resource during adolescence and its associations with personal characteristics and sexual behaviors of youths. Data were obtained from a self-administrated Swiss national survey on sexuality among young adults (mean age 26.3). Participants (N = 4978) were divided into six groups according to their main SE resource during their adolescence: Friends (1939; 38.9%), Parents (1361; 27.3%), School (n = 949; 19.1%), The Internet (399; 8.0%), Nobody (172; 3.5%) and Other (157; 3.2%). Groups were compared on sociodemographic, first sexual experiences, pregnancy, risky sexual behaviors, and undesired sexual experiences data. Males and non-heterosexual participants were overrepresented in the Internet group while, females more often reported their parents as their main SE resource. Participants in the School group reported the lowest rates of sexually transmitted infections and Friends the highest. Compared to the School group, those in the Friends, Internet, Nobody, and Other groups were more likely to report undesired sexual experiences. Few differences appeared between parents and school. Even though some resources such as friends or the Internet presented negative outcomes when they were assessed individually, we cannot deny the important place that they occupy in the lives of some youths.